1998
DOI: 10.1902/annals.1998.3.1.350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Functional Changes of Periodontal Tissue Cells

Abstract: Although the severity of periodontal disease is known to be affected by age, functional changes of periodontal tissue cells during the aging process are not well characterized. It is important to define how cellular aging affects the progression of periodontal diseases associated with the aging process. In vitro aging of human gingival fibroblast (HGF) and periodontal ligament fibroblast (HPLF) cells was prepared by sequential subcultivations (5 to 6 passages as young, 18 to 20 passages as old). GFs were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 68 publications
3
69
0
4
Order By: Relevance
“…There are phenotypic subpopulations of fibroblasts with different functions in the synthesis and maintenance of extracellular matrix constituents 10 . In vivo and in vitro studies have shown functional and structural alterations in fibroblasts associated with ageing 6,[11][12][13] . Gingival fibroblasts (GF) may be constantly affected by oral bacteria and their products, such as the lipopolysaccharides (LPS), present in their cell walls.…”
Section: Age-dependent Changes Of the Periodontal Tissuesmentioning
confidence: 99%
See 4 more Smart Citations
“…There are phenotypic subpopulations of fibroblasts with different functions in the synthesis and maintenance of extracellular matrix constituents 10 . In vivo and in vitro studies have shown functional and structural alterations in fibroblasts associated with ageing 6,[11][12][13] . Gingival fibroblasts (GF) may be constantly affected by oral bacteria and their products, such as the lipopolysaccharides (LPS), present in their cell walls.…”
Section: Age-dependent Changes Of the Periodontal Tissuesmentioning
confidence: 99%
“…Gingival fibroblasts (GF) may be constantly affected by oral bacteria and their products, such as the lipopolysaccharides (LPS), present in their cell walls. The LPS induces GF to release some inflammatory cytokines such as prostaglandin E 2 (PGE 2 ), interleukin (IL)-1 , and plasminogen activator (PA) 6,14 . The influence of these inflammatory mediators on both GF and periodontal ligament fibroblasts (PLF) might account for the severity of periodontal disease 6 .…”
Section: Age-dependent Changes Of the Periodontal Tissuesmentioning
confidence: 99%
See 3 more Smart Citations